2010
DOI: 10.1128/aem.01988-09
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Speciation in the Genus Bacillus

Abstract: Microbial ecologists and systematists are challenged to discover the early ecological changes that drive the splitting of one bacterial population into two ecologically distinct populations. We have aimed to identify newly divergent lineages ("ecotypes") bearing the dynamic properties attributed to species, with the rationale that discovering their ecological differences would reveal the ecological dimensions of speciation. To this end, we have sampled bacteria from the Bacillus subtilis-Bacillus licheniformis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
194
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(205 citation statements)
references
References 61 publications
7
194
1
3
Order By: Relevance
“…This data set is generated under the assumptions of the Stable Ecotype model, with periodic selection acting as the force of cohesion within ecotypes. We also present the algorithms' demarcations of Bacillus strains in the Radio Facility Wash canyon in Death Valley [2]. Finally, we compare the running times of the algorithms.…”
Section: B the Algorithmsmentioning
confidence: 99%
See 4 more Smart Citations
“…This data set is generated under the assumptions of the Stable Ecotype model, with periodic selection acting as the force of cohesion within ecotypes. We also present the algorithms' demarcations of Bacillus strains in the Radio Facility Wash canyon in Death Valley [2]. Finally, we compare the running times of the algorithms.…”
Section: B the Algorithmsmentioning
confidence: 99%
“…The disadvantage of AdaptML is that it is limited to identifying ecotypes that are significantly different in preferences to habitat types that are anticipated by the investigators. Interestingly, three recent studies have shown that Ecotype Simulation and AdaptML reach highly similar ecotype demarcations [2,28,29], indicating that investigators' a priori guesses about the significant habitat types have been fairly accurate. Finally, a disadvantage of each class of algorithms is that their ability to find the adaptively homogeneous ecotypes is limited by the phylogenetic resolution of the sequences analyzed, and it is difficult to test whether a putative ecotype is homogeneous in its ecological adaptations [4].…”
Section: B the Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations